Maternal-Fetal Pharmacology of Drugs: A Review of Current Status of the Application of Physiologically Based Pharmacokinetic Models - Chaphekar, Nupur; Dodeja, Prerna; Shaik, Imam H.; Caritis, Steve; Venkataramanan, Raman (Frontiers in Pediatrics, 2021)
Pregnancy and the postpartum period are associated with several physiological changes that can alter the pharmacokinetics (PK) and pharmacodynamics (PD) of drugs. Drug dose adjustment may be required during pregnancy and postpartum to achieve drug exposures comparable to what is observed pre-pregnancy. There are limited clinical pharmacology studies in these pregnant and postpartum women due to ethical, fetal safety and legal issues. There is very limited data on fetal exposure of drugs during pregnancy and transfer of drugs via human milk during breastfeeding. Over the past several years, there has been an increase in the application of modeling and simulation techniques such as population PK (PopPK) and physiologically based PK (PBPK) modeling to provide guidance on drug dosing in this special patient population. Population PK models rely on measured PK data, whereas physiologically based PK models incorporate physiological, preclinical, and clinical data to predict drug exposure during pregnancy. These modeling strategies offer a promising approach to identify the drugs with PK changes during pregnancy and thereby guide dose optimization during pregnancy. PBPK is also being utilized to predict the fetal exposure of drugs and drug transfer via human milk following maternal exposure. This review focuses on PBPK modeling to predict maternal and fetal exposure of drugs and thereby guide drug therapy during pregnancy.